Oral microbial taxa associated with risk for SARS-CoV-2 infection - Callahan, Nicholas; Hattar, Meryana; Barbour, Thawab; Adami, Guy R.; Kawar, Nadia (Frontiers in Oral Health, 2022)
Abstract Hypothesis and Objective: The oral and digestive tract microbial ecosystem has sparked interest because of its impact on various systemic diseases and conditions. The oral cavity serves not only as a reservoir for many potentially virulent microbiota but also as an important entry point and portal to the human body system. This is especially significant in the transmissibility of the virulent current pandemic virus SARS-CoV-2. The oral and digestive microbiome influences the inflammatory burden and effectiveness of the immune system and serve as markers of activity of these host processes. The host immune response plays a role in infection susceptiblity including SARS-CoV-2. The purpose of this study is to investigate the role of specific salivary oral microbiome in susceptibility to SARS-CoV-2 infection. Methods and Results: 106 subjects of known medical and dental history who consented to provide saliva samples between Jan 2017 and Dec 2019 were included in this study. 16 had become COVID-19 positive based on PCR test by 3/01/2021. A comparison of oral microbiome bacteria taxa profiles based on 16S rRNA sequencing revealed differences between the two groups in this pilot study. Conclusions: These bacteria taxa may be associated with risk for SARS-CoV-2 infection in the unvaccinated population.